The Common Hallmarks and Interconnected Pathways of Aging, Circadian Rhythms, and Cancer: Implications for Therapeutic Strategies - Jie Wang; Fanglin Shao; Qing Xin Yu; Luxia Ye; Dilinaer Wusiman; Ruicheng Wu; Zhouting Tuo; Zhipeng Wang; Dengxiong Li; William C. Cho; Wuran Wei; Dechao Feng (Research)
The intricate relationship between cancer, circadian rhythms, and aging is increasingly recognized as a critical factor in understanding the mechanisms underlying tumorigenesis and cancer progression. Aging is a well-established primary risk factor for cancer, while disruptions in circadian rhythms are intricately associated with the tumorigenesis and progression of various tumors. Moreover, aging itself disrupts circadian rhythms, leading to physiological changes that may accelerate cancer development. Despite these connections, the specific interplay between these processes and their collective impact on cancer remains inadequately explored in the literature. In this review, we systematically explore the physiological mechanisms of circadian rhythms and their influence on cancer development. We discuss how core circadian genes impact tumor risk and prognosis, highlighting the shared hallmarks of cancer and aging such as genomic instability, cellular senescence, and chronic inflammation. Furthermore, we examine the interplay between circadian rhythms and aging, focusing on how this crosstalk contributes to tumorigenesis, tumor proliferation, and apoptosis, as well as the impact on cellular metabolism and genomic stability. By elucidating the common pathways linking aging, circadian rhythms, and cancer, this review provides new insights into the pathophysiology of cancer and identifies potential therapeutic strategies. We propose that targeting the circadian regulation of cancer hallmarks could pave the way for novel treatments, including chronotherapy and antiaging interventions, which may offer important benefits in the clinical management of cancer.